Parent-School Collaboration and Its Role in Facilitating Research Participation of Students with mild Intellectual Disability: A Cross-Sectional Survey - Oluwaseun Omowumi, Akin-Fakorede; Anake, Paulina Mbua; Ayin, Nnyenkpa Ntui; Igajah Ndaro, Mayen Ndaro; Obisessong, Vera Mpuon; Sylvanus, Umoh Margaret; Wanbikom, Princess Esther; Abang, Thomas Agbor; Echu, Alice Etim; Orim, Faith Sylvester; Okoh, Affiong Sunday; Abuo, Cyril Bisong; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Introduction: Inclusive education emphasizes the need for students with intellectual disabilities (ID) to participate actively in all academic activities, including research. Despite this ideal, students with mild intellectual disabilities (MID) often face obstacles that hinder their engagement, revealing significant gaps in equal access to educational opportunities. Previous studies suggest that collaborative partnerships between parents and schools can play a vital role in promoting meaningful participation; however, there is limited empirical evidence on the effectiveness of these collaborations in supporting research engagement among students with MID. Purpose of the Study: The primary objective of this study was to investigate the impact of parent-school collaboration on research participation among students with MID. In particular, the study sought to determine how teacher involvement, parental engagement, school-home communication, and parental provisions collectively and individually predict students’ participation in research activities. Methods: This research employed a cross-sectional survey approach, gathering data from 437 students with mild intellectual disabilities enrolled in public schools in Cross River State, Nigeria. A quantitatively validated questionnaire was used to ensure the reliability and validity of the data collected. Analyses included descriptive statistics, one-sample t-tests, and multiple regression to examine the relationships and predictive power of the identified factors. Findings: The findings revealed that students with MID generally demonstrated low levels of participation in research activities. Collectively, parental engagement, teacher involvement, school-home communication, and parental provisions influenced research participation. Among these factors, teacher involvement was the most influential predictor, followed by parental engagement and provisions, whereas school-home communication contributed the least. Conclusions: The study highlights the vital role that both educators and parents play in promoting research participation among students with MID. The results have implications that extend beyond the local context, highlighting global challenges in ensuring equitable academic opportunities for students with intellectual disabilities and underscoring the importance of promoting inclusive education practices. Implications: From a theoretical perspective, the study enhances existing models of inclusive education by clarifying the relative impact of school- and family-based support on research participation. Practically, it highlights the need for targeted teacher training, structured programs to promote parental involvement, and enhanced school-home communication channels. Policymakers are encouraged to adopt inclusive research participation guidelines to cultivate supportive learning environments, ultimately enhancing students’ academic development, engagement, and long-term outcomes.